Powered swing-by in the elliptic restricted problem - Ferreira, Alessandra F. S.; Prado, Antonio F. B. A.; Winter, Othon C. [UNESP] (My University, 2014)
This paper studies maneuvers for a spacecraft that combines an impulse with a Swing-By performed with a celestial body that is traveling in an elliptical orbit around the primary body of the system. The objective is to measure the variations of the velocity, energy and angular momentum of the spacecraft due this maneuver. An algorithm is developed to obtain the energy and the angular momentum variation for this particular type of powered Swing-By. In this way, it is possible to find the best direction and instant to apply the impulse in order to maximize the energy variation. The results show that applying the impulse in the direction of the motion of the spacecraft is generally not the optimal solution and the results depends on the position of the secondary body in its orbit around the main body and the eccentricity of the orbits of the primaries. Compared to the circular case, several situations where the impulse is retrograde appears when the secondary body is at the periapsis of its orbit, due to the larger gains that can be obtained from the new geometry of the Swing-By.